MODEL AFL UNTUK MENINGKATKAN PEMAHAMAN DAN HIGHER ORDER THINKING SKILLS MAHASISWA VOKASI BIDANG BUSANA - Widihastuti, Widihastuti; Suyata, Suyata (Jurnal Penelitian dan Evaluasi Pendidikan, 2014)
Penelitian ini bertujuan: (1) mengembangkan model AFL berbasis HOTS untuk pembelajaran bidang busana di perguruan tinggi; (2) menguji keefektifan model AFL berbasis HOTS dalam meningkatkan pemahaman dan HOTS mahasiswa pendidikan vokasi bidang busana. Penelitian pengembangan ini menggunakan HC-ADDIE modification model. Tahapan research meliputi analysis & need assessment. Tahapan development meliputi design prototype model, validasi model, uji keterbacaan, melatih  dosen,  uji coba terbatas dan diperluas sebagai implementation, analysis, dan evaluation melalui CAR. Tahapan diffusion meliputi diseminasi hasil penelitian melalui seminar dan jurnal. Subjek uji coba adalah mahasiswa S1 Pendidikan Teknik Busana, Fakultas Teknik, UNY. Analisis data menggunakan teknik statistik deskriptif kuantitatif dengan penyajian data berupa tabel, grafik, dan diagram, serta menggunakan teknik statistik inferensial yaitu one-way ANOVA, dengan bantuan program Excell dan SPSS for Windows 17.0. Hasil penelitian menunjukkan: (1) model AFL berbasis HOTS berhasil dikembangkan melalui HC-ADDIE modification model; (2) model AFL berbasis HOTS terbukti efektif untuk meningkatkan pemahaman dan HOTS mahasiswa.Kata kunci: AFL, HOTS, mahasiswa vokasi bidang busana_____________________________________________________________THE AFL MODEL TO IMPROVE UNDERSTANDING AND HIGHER ORDER THINKING SKILLS OF STUDENTS OF CLOTHING IN COLLEGEAbstractThis study aims: (1) to develop a model of HOTS-based AFL to the teaching and learning of clothing in college; (2) to investigate the effectiveness of the developed model of HOTS-based AFL to improve understanding and HOTS of student of clothing vocational education. This study is a development research, using HC-ADDIE modification model that is the collaboration and modification of the research, development, and diffusion of Hopkins & Clark model with ISD-ADDIE model and the classroom action research. The stages of research include analysis and needs assessment. The stages of development include designing prototype models, validating model, testing reliability, training lecturer/observer, conducting limited and extended trials as implementation, analysis, and evaluation through the classroom action research. The stages of diffusion include the dissemination of research results through seminars and journals. The subjects of this study were under graduate student teachers majoring in the field of clothing of vocational education in the first semester of 2012/2013 at Clothing Technical Education Program, Faculty of Engineering, Yogyakarta State University. The data analysis used the descriptive statistical techniques with the presentation in the form of tables, graphs, and diagrams, as well as using inferential statistical techniques namely one-way ANOVA. The process of data analysis used Excel and SPSS for Windows 17.0 program. The results of this study are as follows: (1) The HOTS-based AFL model for the teaching and learning of clothing to the student of clothing vocational education is successfully developed through the HC-ADDIE modification model. (2) The HOTS-based AFL model is effective to improve the students' understanding and students' HOTS.Keywords: AFL, HOTS, student of clothing vocational education